Endemismo regional presente en la flora del municipio de Culiacán, Sinaloa, México - Vega-Aviña, Rito; Aguiar-Hernández, Hipólito; Gutiérrez-García, Juan Antonio; Hernández-Vizcarra, Jorge Alejandro; Vega-López, Inés Fernando; Villaseñor, José Luis (Instituto de Ecología, A.C., 2000)
The municipio of Culiacán has an area of 4758.9 km2 and is located in the central portion of the state of Sinaloa. Its topography is relatively flat, with a large percentage of its surface occurring below 300 m of altitude and only few places surpass 500 m above sea level. The main vegetation type is the thorn forest; however, the mangrove forest, the tropical deciduous forest, the tropical subdeciduous forest, the Quercus forest, and the Pinus and Quercus forest are also present although in less proportion. An inventory of the vascular flora recorded 1 445 native species and subspecific taxa, in 623 genera and 145 families. 162 endemic taxa to western (W) and northwestern (NW) regions of Mexico are present in the municipio of Culiacán, two of them being restricted to its political borders. In this paper, a checklist of the endemic taxa to W and NW Mexico occurring in the municipio is presented; their distribution patterns at state level in the region are also discussed.